Proposed practical protocol for flow cytometry analysis of microglia from the healthy adult mouse brain: Systematic review and isolation methods’ evaluation - Srakočić, Sanja; Josić, Paula; Trifunović, Sebastijan; Gajović, Srećko; Grčević, Danka; Glasnović, Anton (Frontiers in Cellular Neuroscience, 2022)
The aim of our study was to systematically analyze the literature for published flow cytometry protocols for microglia isolation and compare their effectiveness in terms of microglial yield, including our own protocol using sucrose for myelin removal and accutase for enzymatic digestion. For systematic review, the PubMed was searched for the terms “flow cytometry”, “microglia”, “brain”, and “mice”. Three different myelin removal methods (Percoll, sucrose and no removal) and five protocols for enzymatic digestion (accutase, dispase II, papain, trypsin, and no enzymatic digestion) were tested for the effectiveness of microglia (CD11b+CD45int cell population) isolation from the adult mouse brain using flow cytometry. Qualitative analysis of the 32 selected studies identified three most commonly used myelin removal protocols: Percoll, the use of myelin removal kit, and no removal. Nine enzymatic digestion protocols were identified, from which we selected dispase II, papain, trypsin, and no enzymatic digestion. A comparison of these myelin removal methods and digestion protocols showed the Percoll method to be preferable in removal of non-immune cells, and superior to the use of sucrose which was less effective in removal of non-immune cells, but resulted in a comparable microglial yield to Percoll myelin removal. Digestion with accutase resulted in one of the highest microglial yields, all while having the lowest variance among tested protocols. The proposed protocol for microglia isolation uses Percoll for myelin removal and accutase for enzymatic digestion. All tested protocols had different features, and the choice between them can depend on the individual focus of the research.